Hepatitis B Virus Infection Knowledge as a Predictor of Vaccination Uptake Intentions Among Healthcare Workers in the Oti Region, Ghana - Solomon Tagbor RN, MPIL; Lillian Akorfa Ohene RN, PhD; Charles Ampong Adjei RN, PhD; Vivian Efua Senoo-Dogbey RN, PhD; Josephine Mpomaa Kyei RN, PhD (SAGE Open Nursing)
Background Hepatitis B virus (HBV) infection is one of the world's most important public health issues. Vaccination remains the mainstay for preventing HBV transmission. Among health care workers, adequate knowledge of HBV infection has the potential to induce the motivation to vaccinate against the disease. This study aimed to assess the knowledge of HBV and its influence on vaccination intentions. Methods A descriptive cross-sectional survey was undertaken, and healthcare workers were randomly recruited from two healthcare facilities. A pretested, structured questionnaire with three domains was used to collect data in a self-administered interview session. Data entry, cleaning, and analysis were performed using SPSS. Descriptive statistics were performed to summarize the data. Reliability tests, Pearson correlation analysis, and multiple linear regression analysis were performed to identify the correlation and predictive relationships. Results The mean age and mean period of professional experience were (SD 31.20 ± 5.25) years and 4.64 (±3.95) years, respectively. The overall reliability coefficient of the combined scale was α = .83. The participants demonstrated satisfactory knowledge of the disease and its causation, transmission, consequences, and prevention, giving correct responses predominantly on 12 out of 15 domains with a knowledge mean score of 11.65 ± 0.91. The participants also had good intentions for HBV vaccination (3.58 ± 0.22). There was a positive correlation between HBV knowledge and vaccination uptake intentions ( r  = .33, p  < .01). Hepatitis B knowledge significantly predicted vaccination uptake intentions (β = .23, t  = 2.88, p  < .01). Conclusion The study found that healthcare workers had a satisfactory level of knowledge about HBV infection. Most participants correctly identified key aspects of the disease, including its causation, transmission, consequences, and prevention. Importantly, higher knowledge levels were significantly associated with stronger vaccination uptake intentions, as demonstrated by a positive correlation and a predictive relationship.